Dynamic relationship of exchange rates and crude oil prices in South Africa: are there asymmetries? - Ali, Hamisu Sadi; Mukhtar, Umar; Tijani, Bulama Abiso; Auwal, Abdullahi Muhammad (International Institute for Science, Technology & Education, 2015)
We estimated the relationship between the exchange rates and crude oil prices for the period of 1960 to 2013. Based on Engle-Granger we found that the variables are cointegrated means there exist long-run relationship. However, when we move on to TAR and MTAR models the findings are opposite as there is no element of cointegration and the speed of adjustment is symmetric. This shows that based on TAR and MTAR models the effects of exchange rates on crude oil prices is insignificant. The policy relevance is that South African authority need to monitor its exchange rates persistently related to other currencies more especially American dollar because it determined the crude oil prices that might have greater influences on other macroeconomic variables.